2023
DOI: 10.1002/kpm.1759
|View full text |Cite
|
Sign up to set email alerts
|

Contextual factors influencing knowledge sharing and application in the care and support for people with intellectual disabilities during the COVID‐19 pandemic

Abstract: During the COVID‐19 pandemic, support workers and health professionals caring for and supporting people with intellectual disabilities (ID) required new knowledge on, for example, treatment and infection prevention. ID care organizations had to quickly share up‐to‐date knowledge and encourage its application. This study explored the contextual factors influencing knowledge sharing and application in the care and support for people with ID, contrasted their relevance prior to and during the pandemic, and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…At the organizational level, there are approximately 170 service organizations across the Netherlands for people with mild to profound ID. Direct care and support are provided by professionals from multiple disciplines such as care staff, psychologists, and (para)medics (Kersten et al, 2023). Several academic research departments and care-provider organizations set up partnerships in Academic Collaboratives (ACs).…”
Section: Study Settingmentioning
confidence: 99%
See 4 more Smart Citations
“…At the organizational level, there are approximately 170 service organizations across the Netherlands for people with mild to profound ID. Direct care and support are provided by professionals from multiple disciplines such as care staff, psychologists, and (para)medics (Kersten et al, 2023). Several academic research departments and care-provider organizations set up partnerships in Academic Collaboratives (ACs).…”
Section: Study Settingmentioning
confidence: 99%
“…Furthermore, by tapping into each other's expertise, knowledge can be co-created (Embregts et al, 2020). Previous research showed that the contextual factors relevant for knowledge sharing and application before the pandemic (e.g., the leadership of professionals and user-friendliness of interventions) also played an important role in processing knowledge during the pandemic (Kersten et al, 2023). For example, a registry was launched for COVID-19 among people with ID, which was a joint initiative of an AC and the Ministry of Health, Welfare, and Sports in the Netherlands (Koks-Leensen et al, 2023).…”
Section: Roles and Collaboration In Knowledge Managementmentioning
confidence: 99%
See 3 more Smart Citations